2009
DOI: 10.1136/thx.2009.116376
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lung T cell responses aid the rapid diagnosis of pulmonary tuberculosis

Abstract: Background: The diagnosis of smear-negative pulmonary tuberculosis (TB) is problematic. There are limited data on the profile of alveolar TB antigen-specific T cells, and their utility for the rapid immunodiagnosis of pulmonary TB is unclear. Methods: Antigen-specific interferon c (IFNc) responses to the RD-1 antigens ESAT-6 and CFP-10 (T-SPOT.TB and QuantiFERON-TB-Gold-In-Tube), heparin-binding haemagglutinin and purified protein derivative were evaluated, using alveolar lavage cells, in 91 consecutively recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 29 publications
(48 reference statements)
5
72
0
Order By: Relevance
“…Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used. Among the 13 articles, the NPV ranged between 74.4% [36] and 100% [22,34], with a pooled value of 94% (95% CI 92.1-95.6%) for the T-SPOT1.TB and 88% (95% CI 84.6-91.5%) for the QFT-G-IT (figs 2 and 3).…”
Section: Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used. Among the 13 articles, the NPV ranged between 74.4% [36] and 100% [22,34], with a pooled value of 94% (95% CI 92.1-95.6%) for the T-SPOT1.TB and 88% (95% CI 84.6-91.5%) for the QFT-G-IT (figs 2 and 3).…”
Section: Specificitymentioning
confidence: 99%
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to quantify the frequency of antigen-specific effector cells at the site of disease rather than in whole blood. This approach has recently been shown to be highly accurate when using bronchial alveolar lavage lymphocytes to diagnose pulmonary TB (22)(23)(24) but not when using site-specific lymphocytes to diagnose pleural TB (25). Case reports and small series suggest that this approach may also be useful for the diagnosis of TBM (26)(27)(28)(29).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…A count of 20 or higher SFCs per million cells in the ESAT-6 or CFP-10 wells was deemed a positive result (see online supplement for further details). Given the use of different cut points in specific body compartments (22,25) when compared with peripheral blood and that none has been defined for CSF, which has unique physiologic and anatomic characteristics, we derived new cut-offs using receiver operating characteristic (ROC) curves analysis. The manufacturer's cut-off and cut-offs generated from the study were used for reporting results.…”
Section: Csf Lymphocyte Antigen-specific Ifn-g Responsesmentioning
confidence: 99%